Use of non-selective β-blockers is associated with decreased tumor proliferative indices in early stage breast cancer - Montoya, Alexa (Oncotarget, 2016)
Previous studies suggest beta-adrenergic receptor (β-AR) antagonists (β-blockers) decrease breast cancer progression, tumor metastasis, and patient mortality; however the mechanism for this is unknown. Immunohistochemical analysis of normal and malignant breast tissue revealed overexpression of β1-AR and β3-AR in breast cancer. A retrospective cross-sectional study of 404 breast cancer patients was performed to determine the effect of β-blocker usage on tumor proliferation. Our analysis revealed that non-selective β-blockers, but not selective β-blockers, reduced tumor proliferation by 66% (p < 0.0001) in early stage breast cancer compared to non-users. We tested the efficacy of propranolol on an early stage breast cancer patient, and quantified the tumor proliferative index before and after treatment, revealing a propranolol-mediated 23% reduction (p = 0.02) in Ki67 positive tumor cells over a three-week period. The anti-proliferative effects of β-blockers were measured in a panel of breast cancer lines, demonstrating that mammary epithelial cells were resistant to propranolol, and that most breast cancer cell lines displayed dose dependent viability decreases following treatment. Selective β-blockers alone or in combination were not as effective as propranolol at reducing breast cancer cell proliferation. Molecular analysis revealed that propranolol treatment of the SK-BR-3 breast cancer line, which showed high sensitivity to beta blockade, led to a reduction in Ki67 protein expression, decreased phosphorylation of the mitogenic signaling regulators p44/42 MAPK, p38 MAPK, JNK, and CREB, increased phosphorylation of the cell survival/apoptosis regulators AKT, p53, and GSK3β. In conclusion, use of non-selective β-blockers in patients with early stage breast cancer may lead to decreased tumor proliferation.